KOHESI DAN KOHERENSI DALAM NOVEL KKN DI DESA PENARI KARYA SIMPLEMAN DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA DI SMA - Ismi Isma Wati; Sri Mulyati Mulyati; Khusnul Khotimah Khotimah (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2021)
Cohesion and coherence have an important role in writing essays, both those that will write or those that have become essays. Therefore this study aims to determine the use of cohesion and coherence in the KKN novel in Penari Village. The object of this research is the KKN novel in Penari Village by Simpleman. The subject of this research is the sentence which contains the type of cohesion and coherence in the KKN novel in Penari Village by Simpleman. The approach used is a qualitative approach. A qualitative approach is an approach that presents data in the form of sentences. The design of this research is by collecting data, then the data is grouped according to the use of cohesion and coherence types, then the data is analyzed and presented in an informal form. Data collection techniques using reading techniques and note taking techniques. The technique of presenting the results of the analysis using informal techniques. Informal techniques are techniques that present data in the form of common words that are easily understood by the reader. The results of this study are grammatical cohesion, lexical cohesion and coherence types. Grammatical cohesion includes: reference, substitution, ellipsis, and conjunction. The use of lexical cohesion are of two types namely, repetition and collocation. The use of coherence there are five relationships, namely: the sum relationship, the sequential relationship, the resistance relationship, the causal relationship, and the time relationship.